AN ANALYSIS OF THE IMPACT OF HUMAN CAPITAL DEVELOPMENT ON ECONOMIC GROWTH IN NIGERIA - IBRAHIM, MUSA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The study examines the impact of Human Capital Development on Economic Growth in Nigeria from 1989 to 2023. The Zivot-Andrew unit root test indicates that real gross domestic product, interest rate and secondary school enrolment are stationary at first difference while growth capital formation, labour force and tertiary school enrolment are stationary at level. ARDL model shows that that growth capital formation has a positive and statistically significant effect on the real gross domestic product in Nigeria. The labour force shows a positive and statistically significant effect on the real gross domestic product in Nigeria. Secondary school enrolment shows positive and statistically significant effect on the real gross domestic product in Nigeria. Tertiary school enrolment indicates positive and statistically significant effect on the real gross domestic product in Nigeria. The study recommended Nigeria should invest more in human capital development process and endeavours prioritize the education sectors budgeting considering its growth driving potentials in Nigeria. Similarly